(untitled) (Baghdad Science Journal, 2007)
The effect of subinhibitory concentration of Antibiotics on the Adherence of S.aureus (Coagulase Positive Staphylococci), and S.epidermidis (Coagulase negative Staphylococci) and Pseudomonas aeruginosa, Enterobacter cloacae, Citobacter freundi (Gram negative bacteria) was done and the results revealed that Rifampicin was the best antibiotic inhibiting Staphylococci adherence and Vancomycin has less effect on the adherence of Staphylococci, whereas Tetracyclin was the best antibiotic inhbiting Gram negative bacteria adherence and Amikacin has the lest less effect on inhibiting bacterial adherence.